2012
DOI: 10.1093/ajae/aas045
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' Heterogeneous Valuation of Laser Land Leveling in Eastern Uttar Pradesh: An Experimental Auction to Inform Segmentation and Subsidy Strategies

Abstract: Demand heterogeneity often makes it profitable for firms to price and promote goods and services differently in different market segments. When private consumption brings public benefits, this same heterogeneity can be used to develop targeted public subsidies. We explore the design of public-private targeting and segmentation strategies in the case of a resourceconserving agricultural technology in India. To understand farmers' heterogeneous demand for Laser Land Leveling (LLL), we conducted an experimental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…It showed that adopters were equally from each category of land holding size showing scale neutrality and non-biasedness of laser land levelling towards large farmers. Lybbert et al, (2012) in their study observed similar results. There were different costs of hiring of laser leveller under various agencies.…”
Section: Resultssupporting
confidence: 66%
“…It showed that adopters were equally from each category of land holding size showing scale neutrality and non-biasedness of laser land levelling towards large farmers. Lybbert et al, (2012) in their study observed similar results. There were different costs of hiring of laser leveller under various agencies.…”
Section: Resultssupporting
confidence: 66%
“…With larger plots under the SFLF model, irrigations will take longer if supply flow rates are not increased proportionate to the increase in field size, with potential negative effects on yield and WPi from increased waterlogging and longer irrigation time. The study conducted by ( Lybbert et al, 2013 ) in eastern Uttar Pradesh (a neighbouring state of Bihar with similar agricultural landscape including plot size), highlighted an interesting perspective on "willingness to pay" as the main driver for the adoption of laser land levelling rather than plot size. The smallest plot size in their study was ~800 m 2 (compared with ~600 m 2 in our study).…”
Section: Discussionmentioning
confidence: 99%
“…However, the conditional logit model assumes that farmers prefer homogeneity and random items are identical and independent. However, this may be biased by the independence of irrelevant choices [52], and the farmer homogeneity hypothesis differs from reality, with farmers' preferences being heterogeneous [53,54]. To this end, the mixed logit model is considered a more appropriate method to study the decision-making behavior of farmers with heterogeneous preferences.…”
Section: Methodsmentioning
confidence: 99%